2N+3=6-N

Simple and best practice solution for 2N+3=6-N equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2N+3=6-N equation:


Simplifying
2N + 3 = 6 + -1N

Reorder the terms:
3 + 2N = 6 + -1N

Solving
3 + 2N = 6 + -1N

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Add 'N' to each side of the equation.
3 + 2N + N = 6 + -1N + N

Combine like terms: 2N + N = 3N
3 + 3N = 6 + -1N + N

Combine like terms: -1N + N = 0
3 + 3N = 6 + 0
3 + 3N = 6

Add '-3' to each side of the equation.
3 + -3 + 3N = 6 + -3

Combine like terms: 3 + -3 = 0
0 + 3N = 6 + -3
3N = 6 + -3

Combine like terms: 6 + -3 = 3
3N = 3

Divide each side by '3'.
N = 1

Simplifying
N = 1

See similar equations:

| 4/3x=8/9 | | 7.5-0.25x=0 | | n/2+7=22 | | x+5/6=9/4 | | 87-3x=42x+17 | | 4=-4(4p-9) | | a+1.2=5.2 | | 2s-8-7=-19 | | 25-3/7x=19+4/7x | | 2(s-4)-7=22 | | N/2=6 | | x+1=6x+11 | | 9x+5-4x=-2 | | (3x+4)(3x+4)=18 | | 3c-2(c-9)=2+2c | | 7x/8-2=x | | 6+(-82)-3= | | -3d-3=-15 | | 0.5x-0.3x-2=-6 | | 14x-48=13x-21 | | 4d+c-d= | | -8-6=12-10x | | 5/6x+18-1/6x=6 | | -34-2x=10x | | 20a^2-39a+18=0 | | -5/69= | | 3.3d=23.43 | | 2b^2-3=5b | | 3c-2c-18=2+2c | | 7(5x-72)= | | 5x^2-4x=-1 | | d/6=5 |

Equations solver categories